The law's authority to implicitly inscribe the rhetoric of forgiveness through creatures of statute tasked with truth recovery, justice, peace and reconciliation in post-conflict contexts of South Africa and Rwanda - Teele, Thapelo (Department of Private Law, 2023)
This thesis presents a socio-legal approach of the rhetoric of law and the rhetoric of forgiveness in bodies legally mandated with reconciliation in post-conflict contexts of South Africa and Rwanda. Through a qualitative engagement with literature, the aim is to ascertain whether the law has the authority to grant forgiveness to a perpetrator on behalf of a victim? This question is premised on an understanding of reconciliation as occurring between two individuals in the presence of a third party in view of a specific political outcome, whereas forgiveness is personal, occurring without a specific political outcome and only between two individuals. It is argued that there exists a rhetorical gap between those who speak the language of the law on reconciliation, and those who speak the everyday language of forgiveness informed by a Judaeo-Christian rhetorical frame. It is argued that the gap is addressed by public deliberation or “live rhetoric”, allowing for a divided citizenry in post-conflict contexts to create a transformation (metanoia) and sameness of intent (homonia) in their community that prevents stasis – a reciprocal threat of civil war due to a difference of opinion. “Live rhetoric” functions to keep everyone bound in the process towards reconciliation, and this thesis seeks to highlight that live rhetoric is significant not only for the maintenance of peace and democracy in post conflict contexts at the level of the state, but also allows processes of reconciliation and possibly forgiveness to continue among individuals beyond the confines of bodies legally mandated with reconciliation.